Factors affect for technology usage on information searching - Karunarathna, H.K.G.M.N.; Dahanayeke, S.N.S.; Tennakoon, T.M.P.A.B. (university of Jaffna, 2014)
Information technology has appeared as emerging technology in todays' business, the technology is used to make decisions of day to day life easy and accurate manner. Different areas of theses technology have affected for office automation, new technology application, changing of business process rationally. Researches of Technology impact investigates, measures, find consequences of technology on business, society and find problems, propose solutions for enrich human life. This research focuses attention on Information asymmetry and factors effect for technology using which is vital for decision making of business and community. Research evidences prove that the technology reduces the information asymmetry among different decision makers. The source of such technologies that help, enhance information flow: internet and world wide web, mobile technology etc. At present there exists a trend among Most of the product producers, suppliers to use these technologies as a technique for customer relation handling and increasing sales. Even though information such as price, different design and facilities are available people seems reluctant to use those resources before meet the supplier, this was identified in initial survey. This issue is important and interesting to study further. This study investigates the factors effect to impact underutilize of information resource for buying behavior. For studying the above problem, the domain or area of interest were considered as internet users in Central and North central provinces in Sri Lanka, random sampling method were used and on sample size is 36 and 50 questionnaires were distributed 36 were collected and descriptive mean standard deviation, inferential statics correlation were used to analyze and inference about the research. SPSS tool was used as supportive tool to analyze, present with data collected. Results show that Degree Applying technology is affected with factors: “Importance” and “Barriers and Challenges”. Also marketing programs about information sources and more human friendly information sources help to enhance the usage of information sources more effectively. Improving technology usage will enhance the economy of customers and producers and end entire society.
Keywords: Information asymmetry; Information flow; Blogs; Social networks; Knowledge sharing